Review of techniques for monitoring patient vital signs used by intensive care nurses - part two - Ulenberg, Grzegorz; Ulenberg, Agata; Czapiewski, Łukasz; Humańska, Marzena; Kaczmarek, Wojciech (Journal of Education, Health and Sport, 2018)
The work consists of three parts, which discusses such matters relating to the functioning of the cardiovascular, respiratory and central nervous system. A nurse is a person who is directly involved in the conduct, measures and draws attention to possible complications, since it is she is the person who spends the most time at the bedside. Development of medical science involves the construction of specialized medical equipment ever more perfect, more expensive, more complicated to build and operate, requiring more and more qualifications treatment team.